Nas águas do turismo tem gentes encantadas: duas temporalidades na teia da memória das Comunidades do município de Barreirinhas - MA - Ramos, Carmem Barroso (Universidade do Vale do Rio dos Sinos, 2018)
This thesis analyzes the sociocultural dynamics of the communities on the banks of the Preguiças river, in the Lençóis Maranhenses region. In this process, through the use of oral and sociocultural history, we focus on two temporalities of distinct practices: one where secular traditions were constructed from their narratives (histories, causes and proverbs), a self sustainable economy, their family celebrations, relationships and their slow time; the other is quick time, crowds, spectacles, profitable trade, real estate speculation, tourism. These two times, these two cultures, these two values bring about changes and conflicts. The incoming values try to override the "old values". The interferences of the tourism change the routines, the relations with the time and with the own history of the communities. Thus, from the immersion in the villages of São Domingos, Boa Vista, Mangaba and Atins, being these emblematic in this process, we seek the understanding of the interferences and permanences of the local traditions.
Keywords: Memória; Comunidades Ribeirinhas; Narrativas; Interferências; Lençóis Maranhenses; Memory; Riverside communities; Narratives; Interferences; Lençóis Maranhenses; ACCNPQ::Ciências Humanas::História